N addition increased microbial residual carbon by altering soil P availability and microbial composition in a subtropical Castanopsis forest - Fan, Yuexin; Yang, Liuming; Zhong, Xiaojian; Yang, Zhijie; Lin, Yanyu; Guo, Jianfen; Chen, Guangshui; Yang, Yusheng (Geoderma, 2020)
•Nitrogen addition significantly increased amino sugars and their contribution to SOC.•Nitrogen addition significantly increased Mehlich-P but decreased organic P.•Nitrogen addition increased fungal biomass and acid phosphatase activity.•Soil P availability influenced amino sugars through increasing fungal biomass. Microbial residual carbon (C) plays a crucial role in soil organic C (SOC) stabilization, and exogenous nutrients have frequently been observed to increase the proportion of microbial residual C in soils with limited nitrogen (N). However, how microbial residual C responds to N deposition and their mechanisms in subtropical forest soil with low phosphorus (P) availability remains poorly understood. To fill this knowledge gap, an experiment with 5.5 consecutive years of N addition (control, 40 and 80 kg N ha−1y−1) to a Castanopsis carlesii forest in Fujian, China was performed. Soil properties (e.g., soil C, N, P, and pH), amino sugars (biomarkers of microbial residual C), phospholipid fatty acids (PLFAs), and enzyme activities were investigated. We found that N application and soil depths had significant interactive effects on amino sugars, the PLFAs, and soil enzyme activities. N addition significantly increased the contents of amino sugars and their proportions to soil C in the 0–10 cm soil layer but not the 10–20 cm soil layer (P > 0.05). In addition, glucosamine (GluN), which was mostly derived from fungal cell walls, accounted for 64.9–73.9% of the total amino sugars across three treatments, and the proportion of GluN to total C also increased after N addition in the 0–10 cm layer. These results indicate that N addition elevated the contribution of amino sugars, especially GluN, to soil C sequestration of the 0–10 cm soil layer but not 10–20 cm soil layer. Moreover, N addition significantly enhanced the biomass of fungi and ectomycorrhizal fungi (EMF) and the activities of phosphatase (ACP), phosphodiesterase (PD), N-acetyl glucosaminidase (NAG), acid phenol oxidase (PhOx), and peroxidase (Perox), while it significantly decreased soil organic P (OP) in the 0–10 cm soil layer. These results implied that changes in N:P ratio caused by N addition contributed to the increases of EMF and fungi, which have high P acquisition ability, this in turn enhanced soil P availability. The increased microbial biomass of EMF and fungi likely attributed to the increased contribution of amino sugars to SOC accumulation in the studied forest soil. Our study revealed a novel mechanism of soil C sequestration in subtropical forest ecosystems with low soil P under ongoing N deposition.